PENINGKATAN KEMAMPUAN MENULIS PANTUN MELALUI MODEL GROUP INVESTIGATION (GI) DENGAN MEDIA KARTU PADA SISWA KELAS VI UPTD SD NEGERI 10 PEUDADA - Yulis, Sara; Syahrin, Alfi; Fachrurazi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This Classroom Action Research was motivated by the low ability of sixth-grade students at UPTD SD Negeri 10 Peudada, Bireuen Regency, to write pantun, particularly in identifying and applying the structure, rhyme, opening lines (sampiran), content, and the appropriate number of syllables. This problem was attributed to monotonous conventional teaching practices. This study aimed to describe the improvement in students’ ability to write pantun, observe the learning activities, and identify students’ responses through the implementation of the Group Investigation (GI) model assisted by pantun card media. This study employed a qualitative approach using Classroom Action Research based on the Kemmis and McTaggart model, which was conducted in two cycles. Each cycle consisted of four stages: planning, action implementation, observation, and reflection. The subjects of this study were 24 sixth-grade students of UPTD SD Negeri 10 Peudada in the 2025/2026 academic year. Data were collected through tests, observations, interviews, and documentation. The data were analyzed descriptively using percentages of students’ mastery in pantun writing, teacher activities, student activities, and student responses. The success criterion was established at a minimum classical mastery level of 80%, with a Learning Achievement Criteria (KKTP) score of 75. The results showed that students’ pantun writing ability improved in each cycle. In the pre-action stage, the students’ classical mastery was 37.5%, with a mean score of 63.58. After the implementation of the intervention in Cycle I, classical mastery increased to 70.83%, with a mean score of 85.54. In Cycle II, classical mastery reached 83.33%, with a mean score of 90.41, indicating that the success criterion had been achieved. Teacher activity increased from 85.55% in Cycle I to 96.66% in Cycle II, while student activity increased from 82.22% to 94.44%, both categorized as very good. In addition, students responded positively to the learning process because the learning activities were more engaging and enjoyable and helped them generate ideas for writing pantun. Therefore, the implementation of the Group Investigation (GI) model assisted by pantun card media was effective in improving the pantun writing ability of sixth-grade students at UPTD SD Negeri 10 Peudada.